Floating Microspheres: A Prevailing Trend in the Development of Gastroretentive Drug Delivery System - Srikar, Grandhi (Asian Journal of Pharmaceutics (AJP), 2018)
One of the complex processes in the human body is gastric emptying, as it is highly variable which makes the in vivo performance of the drug delivery systems uncertain. To overcome this variability, a controlled drug delivery system with a prolonged gastric residence time of >12 h in the stomach can be of great practical importance for drugs with an absorption window in the upper small intestine. Various gastroretentive drugs are available in the form of tablets, capsules, laminated films, floating microspheres, granules, and powders. The use of microparticulate drug delivery for the oral delivery of drugs has become a prominent method in the present days. Such systems are more beneficial than the single-unit dosage forms. One of the approaches to increase the gastric retention time through multiparticulate drug delivery is floating microspheres. The floating microspheres are gaining attention which results in more reproducible drug absorption and reduced risk of local irritation. These systems give a prolonged and uniform release of the drugs in the stomach. The present review brings together the recent literature with respect to the methods of preparation, characterization, and various parameters affecting the performance of the floating microspheres for the oral route of administration. Microballoons are advantageous when compared to the other floating drug delivery systems as they do not possess a floating lag time.